Quartz vein styles and gold mineralization in the Penjom Gold Mine, Pahang, Peninsular Malaysia / Zakaria Endut - Zakaria, Endut (2016)

(untitled)
The study area (Penjom Gold Deposit, Pahang, Malaysia) lies 30 km east of the major terrane boundary Bentong-Raub Suture within the central belt of Peninsular Malaysia along the NNE trending splay from the Suture line. Host rock is comprised of turbiditic sequence of Early to Late Permian ranging from well bedded siltstone, calcareous shale, carbonaceous shale, tuffaceous sandstone and conglomerate. These sequences were intruded by fine grained and porphyritic medium grained felsite intrusives (222.4 +/- 1.8 Ma). Quartz veins found here are categorized into two main types, namely shear veins and extension veins. Shear veins are ribbon to laminated veins developed only in carbonaceous units and are either thick or very thin units, parallel to bedding or shearing. This vein type is interpreted as formed during folding and thrusting events involving repeated opening of bedding and shearing planes. Associated with shear veins are several types of extensional veins including sub-vertical extensional vein arrays, hydrothermal quartz breccias and stockwork in felsite rocks. NE to NNE thrust-parallel reverse to dextral faults overprinted the earlier D2 event and generated extensional veins of similar morphology, mostly at intersections of sediment-intrusive contact or as shallowly dipping veins within the intrusive bodies. Local NNW fault controls significant mineralization at the west wall of Jalis Corridor in the form of shear vein, massive to sheeted extension vein. Several north-south trending sinistral faults, intercept at the footwall folded sequence initiated mainly after the main veining event interpreted as during D4. Normal sense of movement of the same fault crosscut and displace the vein is occurring during D5 event, are not associated with the above style of veins but locally host barren quartz calcite-veins and are in certain areas associated with the late stage galena. Common alteration minerals based on XRD analysis are fine grain muscovite, chlorite and illite, which is typically characterized the phyllic alteration. Fluid inclusions were analyzed using eleven doubly polished sections of veins including iv two calcite veins and one quartz sample from hanging wall. No measureable fluid inclusions were found in calcite and hanging wall vein. Fluid inclusions fall in two populations. Population 1 is made up of H2O-NaCl were having Thfinal between 145oC and 265oC while population 2 is consist of H2O-NaCl-CO2 fluid inclusions with higher Thfinal from 200oC to 375oC. Sulphides are comprised of pyrite, arsenopyrite, galena, sphalerite and chalcopyrite. Gold is commonly found with galena but also can be found together with early sulphide. Galena samples from two groups (6 from the mineralised zone and 3 from the non mineralised area) have been sampled and analyzed for trace element geochemistry and lead isotopes. The lead isotope ratios for both groups plot around the bulk crustal growth curve of the plumbotectonic model indicating Pb derived from mixed crustal and magmatic sources. Based on the Cumming and Richards (1975) growth curves, two groups of lead can be interpreted as having formed at 250 Ma and 160 Ma. The Penjom gold deposit shows many similarities with other orogenic gold deposits formed in a terrain subjected to compressional to transpressional event. Gold and other metal could be derived from mix metamorphic-magmatic sources migrated from deeper sources and deposited at mid crustal level during the late stages of an orogenic event.